2012
DOI: 10.1021/ja306348d
|View full text |Cite
|
Sign up to set email alerts
|

Pt5Gd as a Highly Active and Stable Catalyst for Oxygen Electroreduction

Abstract: The activity and stability of Pt(5)Gd for the oxygen reduction reaction (ORR) have been studied, using a combination of electrochemical measurements, angle-resolved X-ray photoelectron spectroscopy (AR-XPS), and density functional theory calculations. Sputter-cleaned, polycrystalline Pt(5)Gd shows a 5-fold increase in ORR activity, relative to pure Pt at 0.9 V, approaching the most active in the literature for catalysts prepared in this way. AR-XPS profiles after electrochemical measurements in 0.1 M HClO(4) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
257
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(282 citation statements)
references
References 30 publications
22
257
2
1
Order By: Relevance
“…[39][40][41] In our laboratory we have taken a different approach, namely to study alloys of Pt and rare earths such as Y, Gd, Ce and La. 33,[42][43][44][45][46][47][48] These alloys have a particularly negative heat of formation, which should provide them with long term-kinetic stability against dealloying at the cathode of a fuel cell. Extended surfaces of Pt 3 Y and Pt 5 Gd show particularly high activity for oxygen reduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[39][40][41] In our laboratory we have taken a different approach, namely to study alloys of Pt and rare earths such as Y, Gd, Ce and La. 33,[42][43][44][45][46][47][48] These alloys have a particularly negative heat of formation, which should provide them with long term-kinetic stability against dealloying at the cathode of a fuel cell. Extended surfaces of Pt 3 Y and Pt 5 Gd show particularly high activity for oxygen reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Extended surfaces of Pt 3 Y and Pt 5 Gd show particularly high activity for oxygen reduction. 42,43,47 On the other hand, upon exposure to reaction conditions, alloys such as Pt 2 Y or PtY corroded extensively, due to Y dissolution; this suggests that an excessive amount of Y is detrimental to catalyst stability. 44 Most recently, we demonstrated that Pt x Y is also highly active for the oxygen reduction reaction in nanoparticulate form.…”
Section: Introductionmentioning
confidence: 99%
“…The development of nanostructured Ptbased electrocatalysts is considered to be one of the most effective approaches to resolve these problems [3]. In the sight of composition, Pt based alloys are believed to improve the ORR activity [4][5][6][7][8], because the introduction of other metal compositions modifies the electronic and crystallographic structures of Pt, resulting in the decrease of the binding energy between Pt and oxygen [9]. On the other hand, the shape and morphology of nanocrystals are also of great importance in the development of ORR catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Pt-M nanoalloys supported by carbon black were developed to investigate the dealloying effect of M atoms on Pt surface towards ORR activity in acid medium [215,219]. Recently, supported by theoretical DFT (density functional theory) calculation, Chorkendorff's group reported experimental facts showing that the Pt-RE (RE = rare earth elements) alloys were the most active and stable Pt-based electrocatalysts for ORR [12,[222][223][224]. Therefore, the synthesis of highly and homogeneously dispersed Pt-RE nanoalloys is an interesting phenomenon in the domain of energy conversion.…”
Section: Low Graphitic Carbonmentioning
confidence: 99%